The Rub – El – Hizb Patterns of Petronas Twin Towers as An inspiration on batik design: An ethnomathematics study - Wan Bakar, Wan Norliza; Awang, Junaidi; Omar, Mazni; Mat Jusoh, Nor Asmira (Journal of Islamic, Social, Economics and Development, 2025)
Petronas twin tower is the highest twin tower in the world. Standing at 451.8 meters tall, the iconic landmark features 88 stores with the sky bridge at 41st and 42nd floor. The inspiring skyline symbolizes the nation’s ambition and potential to become a developed nation. This study focuses on the symbol of Rub el Hizb, the basis for the floor plan of Petronas Twin Tower, as the inspiration on batik design. The research was qualitative research with an ethnographic approach. Data obtained through observation, interview, literacy study and documentation, with the triangulation method as data validity. This research examined the mathematical concepts in the development of Rub el Hizb as the inspiration for batik design. The result showed that there were few mathematical concepts found.in the design of rub El Hizb on batik design. Future research can be explored to implement rub El Hizb patterns on different surfaces.